THE POTENTIALLY TOXIC BENTHIC DINOFLAGELLATES ON MACROALGAE AT THE REEF FLAT OF SERIBU ISLANDS, NORTH JAKARTA - INDONESIA - Widiarti, Riani; Murtiningsih, -; Suwarti, -; Mutaqin, Ahmad; Kurnia, Gud Elina (Marine Research in Indonesia, 2008)
The Ciguatera Fish Poisoning (CFP) causing microorganisms were observed at the reef flat of Penjaliran Barat Islands and Pramuka Islands District, Seribu Island National Park, North Jakarta, Indonesia. Of the samples collected, four potentially toxic benthic dinoflagellates species were found, which are Gambierdiscus toxicus, Prorocentrum concavum, Prorocentrum lima, and Ostreopsis lenticularis. The dinoflagellates were found attached on the brown macroalgae Padina and Sargassum. Most of the benthic dinoflagellates from both locations were found in Pramuka Islands District, the inhabitated islands where human activities which could damage the coral reef areas were relatively high. Beside the macroalgae substrate preference of each dinoflagellate species, several environmental factors were also obtained in this research.